EDUKASI BISNIS UNTUK MENGATASI HAMBATAN BISNIS UMKM TEA BREAK DALAM MELAKUKAN PERLUASAN BISNIS - Jati, L. Jatmiko; Kurniawati, Erna Yovi; Wardhana, Helna; Khairi, Widayatul (JUAN: Jurnal Pengabdian Nusantara, 2024)
This activity explores and educates how a company carries out long-term strategic planning in expanding or expanding its business, where in carrying out expansion and expansion there are of course obstacles and obstacles it faces. Therefore, it is important for a company's strategic planning to overcome the obstacles and obstacles faced in expanding and expanding its business so that it remains stable and competitive. This activity focuses on one of the micro, small and medium enterprises, namely the beverage industry company "Tea Break" which is located in Selaparang sub-district, Rembiga, Mataram City. The results of this activity highlight the importance of company strategic planning in carrying out business expansion and expansion as well as how companies deal with the obstacles and obstacles they face. The results show that the education carried out by the Team has increased the understanding of MSME owners in carrying out expansion.